The Metaverse Media Analysis In A Future Of Instructional Strategy - Budi Ahmad Alfaridzi; Chamim Thohari Mahfudillah; Rossy Yatus Sangadah; Achmad Ipnu Taqiuddin (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2023)
Along with the development of the technology and information age, new technology has emerged in the form of AR (Augment Reality) and VR (Virtual Reality), namely 3D digital technology that exists in the Metaverse, so that from this growth era this can affect the world of economics, politics, and education. Thus, Metaverse is proven to be effective and efficient in future learning strategies. besides that, Metavres is an alternative, especially in the world of economics, politics, and education. So with this in mind, in the case study educational researchers have a purpose and are curious about what Metaverse technology is and how influential it will be for the world of education in the future. This research uses qualitative research with a literature research approach (Library Research) by way of describing scientific studies that intersect with the Metaverse and educational strategies. The basis of this research is a combination of several features in Metaverse with educational strategies. Thus making continuity between implementation and process very potent in the future. Keywords: Metaverse, Strategic, Learning